Serum Brain-Derived Neurotrophic Factor, and Plasma Catecholamine Metabolites in People with Major Depression: Preliminary Cross-Sectional Study - Yoshimura, Reiji; Kishi, Taro; Atake, Kiyokazu; Katsuki, Asuka; Iwata, Nakao (Frontiers in Psychiatry, 2018)
Background There are complicated interactions between catecholaminergic neurons and brain-derived neurotrophic factor (BDNF) in the brain. However, no reports have addressed the relationship among 3-methoxy-4-hydroxyphenylglycol (MHPG), homovanillic acid (HVA), and BDNF in the blood. Objective This paper sought to investigate correlations between serum BDNF and plasma levels of MHPG and HVA in people with major depression (MD). Materials and methods A total of 148 patients (male/female 65/83, age 49.5 ± 12.1 years old) who satisfied criteria for MD based on the Diagnostic and Statistical Manual of Mental Disorders IV were enrolled in the present study. Plasma levels of MHPG and HVA were analyzed using high-performance liquid chromatography, and serum BDNF was measured using ELISA. Results No interactions were observed between plasma HVA levels (mean ± SD = 4.5 ± 1.5 ng/mL) and age, sex, HAMD scores, or serum BDNF levels (mean ± SD = 9.8 ± 2.9 ng/mL). No correlations were not also observed between plasma MHPG levels (mean ± SD = 5.9 ± 2.1 ng/mL) and age, sex, the HAMD17 scores (mean ± SD = 22.2 ± 2.9 ng/mL), or serum BDNF levels. Serum BDNF levels were negatively associated with HAMD17 scores. Conclusion The results suggest that there are no significant correlations between catecholamine metabolites and BDNF in the blood for MDD patients.